The existential realities of dancing - Sheets-Johnstone, Maxine (Frontiers in Cognition, 2024)
Can we again learn about ourselves and our surrounding world through dance as we age, thereby promoting our own health? This article documents facts of life showing that “older adults” do not have to learn to be cognitive of their movement, affective dispositions, or surrounding world; they have been experientially cognitive of all by way of tactility, kinesthesia, and affectivity from the beginning. Present-day cognitive neuroscience, concentrating and theorizing as it does on the brain's neuroplasticity, is however deficient in recognizing these experiential realities. Research studies on the brain and behavior, in contrast, demonstrate that coordination dynamics are the defining feature of both neurological and kinesthetic coordination dynamics. These dynamics are central to corporeal concepts, to the recognition of if–then relationships, and to thinking in movement. In effect, the brain is part of a whole-body nervous system. The study proceeds to show that the qualitative dynamics of movement that subtend coordination dynamics are basic to not only everyday movement but also to dancing—to experiencing movement kinesthetically and to being a mindful body. When Merce Cunningham writes that dance gives you that “single fleeting moment when you feel alive” and is not for “unsteady souls” and English writer D. H. Lawrence writes that “[w]e ought to dance with rapture that we are alive, and in the flesh, and part of the living incarnate cosmos,” their words are incentives to those who are aging to awaken tactilely, kinesthetically, and affectively to the existential realities of dance.